Builders' pricing and tendering procedures in Nigeria - Alabi, Oladipo; Milne, John A. (Ibadan, Nigeria : Julab Publishers, 1987)
The aim of this book is to explain in a logical sequence the component parts of an estimate and to give a clear and methodical approach to pricing. The book has been prepared to meet the needs of building contractors who wish to increase their knowledge of estimating and also for students preparing for examinations in degree and diploma courses in building and quantity surveying.
Includes index.
rpm 22/01/2019, ijb, 31/01/2019
Loans
Keywords: Building